Interkulturelle Depressionsforschung im deutsch-chilenischen Doktorandenkolleg: Entstehungsbedingungen depressiver Erkrankungen und Wirksamkeit ihrer psychotherapeutischen Behandlung im Vergleich zwischen Chile und Deutschland - Kämmerer, Annette (Psychotherapeut, 2018)
The postgraduate student lecture course presented in this article, which was carried out in two cohorts from 2007 to 2013 by Prof. Dr. Manfred Cierpka und Prof. Dr. Annette Kämmerer, was initially the result of personal contact particularly between Manfred Cierpka (University of Heidelberg) and his Chilean colleagues Dr. Juan Pablo Jimenez from the Universidad Católica in Santiago de Chile and Dr. Guillermo de la Parra from the Universidad de Chile. Psychology was included due to the cooperation of Annette Kämmerer with Dr. Mariane Krause (Universidad Católica) and Dr. Laura Moncada (Universidad de Chile). From the encounter of these various scientists an intensive academic exchange arose, which ultimately led to the establishment of the “German-Chilean postgraduate student lecture course” and therefore founded a cooperation between the three participating universities, which is still continuing today.
Gesehen am 05.11.2019